Search for galaxy‐ICM interaction in rich clusters of galaxies. Issue 4 (2nd May 2013) - Gu, L.; Gandhi, P.; Inada, N.; Kawaharada, M.; Kodama, T.; Konami, S.; Nakazawa, K.; Shimasaku, K.; Xu, Haiguang; Makishima, K.; Schartel, Norbert
Abstract Based on optical and X‐ray data for a sample of 34 relaxed rich clusters with redshift of 0.1–0.9, we studied the relative spatial distribution of the two major baryon contents, the cluster galaxies and the hot plasmas. Using photometric data taken with the UH88 telescope, we determined the integrated radial light profiles of member galaxies in each cluster using two independent approaches, i.e., the field background subtraction and the color‐magnitude filtering. The ICM mass profile of each cluster in our sample was derived from a spatially‐resolved spectral analysis using XMM‐Newton and Chandra data. When the sample is divided into three subsamples with redshift intervals of z = 0.11–0.22, 0.22–0.45, and 0.45– 0.89, the galaxy light vs. ICM mass ratio profiles for the central 0.65R500 regions were found to steepen from the higher‐ to lower‐ redshift subsamples, meaning that the galaxies become more concentrated in the ICM sphere towards lower redshifts. Besides, the galaxy light vs. total mass ratio profiles also exhibit gradual concentration towards lower redshift. We interpret that the galaxies, the ICM, and the dark matter components followed a similar spatial distribution in the early phase (z > 0.5), while the galaxies have fallen towards the center relative to the ICM and dark matter. Such galaxy infall is likely tobe caused by ICM drag when galaxies move through the ICM, even though the dynamical friction can enhance the infall of the most massive galaxies. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)